13-Valent vaccine serotype pneumococcal community acquired pneumonia in adults in high clinical risk groups - Daniel, Priya; Rodrigo, Chamira; Bewick, Thomas; Sheppard, Carmen; Greenwood, Sonia; McKeever, Tricia M.; Trotter, Caroline; Lim, Wei Shen (Elsevier, 2018)
There is debate regarding the value of vaccinating adults with the 13-valent pneumococcal conjugate vaccine (PCV-13). This analysis was conducted to investigate the risk of PCV-13 serotype community acquired pneumonia (CAP) in hospitalised adults with co-morbid disease and risk factors for pneumococcal disease in the UK.